Strategi Penguatan Sistem Pengendalian Internal Penerimaan Dan Pengeluaran Kas Untuk Menghindari Terjadinya Fraud Pada Kas Perusahaan Nevian Elektronik Wuluhan Kabupaten Jember - Suwarso, Suwarso; Susanti, Indria Yuli; Anam, Khoirul (Program Studi Akuntansi Fakultas Ekonomi Universitas PGRI Argopuro Jember, 2024)
Research with the aim of analysing the strategy of strengthening internal control of cash receipts and disbursements to avoid fraud at the Nevian electronic company in Jember Regency. Approach is used in this research. Data collection techniques are observation, interviews, documentation and literature study. The results showed that the strategy of strengthening the internal control system on cash receipts and disbursements is an organisation that separates duties and responsibilities, an authorisation system, sound practices, and qualified employees. The implementation of internal control elements in cash receipts and disbursements Nevian Elektronik Jember Regency implemented there are three elements, namely a good organisational structure that separates clear tasks in each section. Nevian Elektronik has set the division of authority in authorising company transactions properly. In recording cash receipts and cash expenditure transactions that occur, get prior authorisation from the authorised official, namely the owner of the business in order to provide protection to the company's assets. Healthy practices by applying accounting records to related documents are well implemented. Meanwhile, the element of qualified employees has not been applied specifically to employees who handle cash in terms of employee recruitment.